Pengembangan Game Edukasi Berbasis Android Sebagai Media Pembelajaran Untuk Anak Usia Dini - Raihan Cahya Adi Putra; wahyudi wahyudi; Chris Dwi Yanthy; Elok Wigati; Syarif Fahmi Mauliansyah (Politeknik Negeri FakFak, 2023)
In every early childhood education, children will be more likely to be interested in games that are easy to play and attract attention in which there are colorful animated images that attract attention. At this stage, children will find it easier to remember an animal shape or writing that has attractive colors and communicative and fun shapes, and can also hear the sounds in it. Based on the description above, it is important to make learning media in the form of Bimbel Online educational games which can facilitate the learning process for early childhood with the concept of learning while playing. With the existence of technology like today, it greatly facilitates activities and changes the shape of children's play patterns today, of course, this digital role is expected to be able to make children more positive in playing. The role of parents is also very important in sorting children's games so they don't go in a negative direction. In this way, this application was formed to make it easier for children and divert them to play in this virtual world with this educational game.